A psychometric evaluation of the Italian short version of the Fear of Pain Questionnaire-III: Psychometric properties, measurement invariance across gender, convergent, and discriminant validity - Diotaiuti, Pierluigi; Corrado, Stefano; Mancone, Stefania; Cavicchiolo, Elisa; Chirico, Andrea; Siqueira, Thais Cristina; Andrade, Alexandro (Frontiers in Psychology, 2023)
The Fear of Pain Questionnaire-III (FPQ-III) is a self-assessment instrument developed specifically to measure fear based on various pain stimuli converging on three factors: severe pain, medical pain, and minor pain. It actually remains the most studied and internationally used tool even in its short versions. The aim of this work was to propose a new validation study oriented to confirm the good psychometric properties of a short model of the FPQ-III for the Italian context. A large sample of participants was recruited (n = 1,064). The three factors structure of the 13-item version of the questionnaire was confirmed (χ2 = 148.092, CFI = 0.971, TLI = 0.962, RMSEA = 0.046, RMSEA 90% CI = .037-.056) as well as the measurement invariance across gender. Item internal reliability was satisfactory. In order to examine convergent validity, a further convenient sample (n = 292) was used and variables related to the individual’s pain experience, locus of control and coping orientations were assessed. The results provided evidence of the good predictive validity of the FPQ-III. A final discriminant assessment using experimental manipulation through fear eliciting videos demonstrated that the instrument is suitable in detecting changes in fear of pain induced by specific situational conditions. The scale in this short version is suitable for quickly and efficiently gathering information about the perceived intensity of such anticipatory fears that might affect even the healthy person dysfunctionally.